Engineering and entrepreneurship - Lee , Yee Loon (2010)
This paper reveals the secret history of Silicon Valley and selected survey on engineering and entrepreneurship education. It explores myths and realities about research and disruptive innovation. Personal experience on creating value from research is discussed. The www.1.my venture launched by an engineering graduate of UTHM is revealed. Strategies to exploit intellectual property and expedite commercialization for viable research products are discussed. Creating a culture of innovation for universities and SMI is proposed. Graduates are encouraged to startup with academics as advisors. Smart university-industry (UI) link should be the lasting benefit. Way forward for research and innovation is highlighted.